The effect of a Clinical Decision Support System on the frequency of dose adjustments of anticancer drugs in case of renal or hepatic dysfunction. (July 2022) - Rolvink, José; Gerards, Anne-Loes E; Kater, Arnon P; Swart, Eleonora L; Becker, Matthijs L
Introduction: Dose adjustments in patients with renal or hepatic dysfunction using anticancer drugs are indicated according to guidelines. However, implementation depends on awareness of prescribing physicians. We implemented a Clinical Decision Support System (CDSS), recommending dose adjustments upon electronic prescriptions based on renal and hepatic function. The alert provides a dose adjustment proposal and recent laboratory results. Our objective was to determine the frequency of dose adjustments before and after implementation of this CDSS. Methods: We included all first orders for patients ≥18 years treated with parenteral antineoplastic agents, for whom dosage adjustment is necessary based on renal or hepatic function between February 2018 and January 2019. This study was performed at the department of Clinical Oncology and Hematology of the Amsterdam University Medical Center. We implemented the CDSS August first. All prescriptions were prescribed according to common practice. We analyzed the orders where a dose reduction based on renal or hepatic function was indicated. Results: We included 73 orders before implementation and 99 orders after implementation. Before implementation 21% of doses were reduced in line with the guidelines versus 34% after implementation (p = 0.048). For hepatic dysfunction the proportion changed from 11% to 46% p = 0.011, while there was no effect for renal dysfunction (24% vs. 26% p = 0.75). Conclusion: Dosages are more frequently adjusted in concordance with guidelines in patients with hepatic dysfunction who are treated with parenteral antineoplastic agents after implementation of a CDSS. The change was not seen in patients with renal dysfunction.